Prenatal Diagnosis Preferences of Turkish Women and the Association of their Choices with Temperament - Tulmac, Ozlem B.; Buturak, Visal (Current Women's Health Reviews, 2022)
Objectives: The purpose of this study is to explain which choices Turkish women prefer for prenatal diagnosis more frequently and to find out if there is an association between temperament and decisions through the prenatal diagnostic steps or consistency of decision. Materials and Methods: This is a cross-sectional study on pregnant women who were admitted to our outpatient clinic based on the responses to a self-administered questionnaire at the time of combined test or triple test as the first prenatal screening test. 198 pregnant women completed self-administered questionnaires comprising 131 questions including Temperament Evaluation of Memphis, Pisa, Paris, and San Diego questionnaire (TEMPS-A). Results: Overall, 88.4% of women were willing to learn if there was an anomaly, whereas 4.5% did not, and 7.5% were uncertain. Of the included patients, 87.9% would decide on the screening tests to be performed, 23.2% had a positive attitude on diagnostic tests, and only 13.1% were in favour of termination. No association was found between the temperament scores and positive, negative, and indecisive attitudes of the patients. In addition, there was no relation between being decisive and indecisive, and the temperament scores except for cyclothymic scores. Indecisive attitude to termination was associated with higher cyclothymic scores (5 (1–13) for decisive patients, 7 (0–17) for indecisive patients, p=0.035). Conclusion: We found that affective temperaments measured by the TEMPS-A are not related to the attitudes about prenatal screening or diagnostic tests or termination. Indecisive attitude to termination was associated with higher cyclothymic scores.
Keywords: attitute